Addition of pre‐wetted lightweight aggregate and steel/polypropylene fibers in high‐performance concrete to mitigate autogenous shrinkage. (11th December 2019) - Zhao, Yanhua; Xu, Bohan; Chang, Jianmei
Abstract: The paper investigates the effects of ceramic sand as pre‐wetted lightweight aggregate together with steel fiber (SF) and polypropylene fiber (PPF) on the shrinkage and mechanical properties of high‐performance concrete (HPC). Four replacement levels of fine aggregate with presoaked ceramic sand (0, 10, 15, and 20% in volume) were first adopted to explore the possibility of ceramic sand as an internal curing material. Thereafter, SF and PPF were added for the replacement level 20% to study the combining effects of internal curing technology and fibers on the shrinkage and mechanical properties of HPC. The results show that the inclusion of pre‐wetted ceramic sand in HPC decreased autogenous deformation, and the risk of cracking in HPC under restrained conditions could be also effectively reduced. But the improvement in dimensional stability was achieved at the cost of deteriorated mechanical properties of HPC. Favorably, internal curing technology combined with SF/PPF could be a better solution for this contradictory: significantly reducing autogenous deformation, prolonging the onset time of crack, decreasing crack width, and cracking area without compromising mechanical properties of HPC.